Probiotics, prebiotics, and synbiotics in chronic constipation: Outstanding aspects to be considered for the current evidence - Araújo, Maísa Miranda; Botelho, Patrícia Borges (Frontiers in Nutrition, 2022)
This integrative aimed to evaluate the effects and the potential mechanism of action of prebiotics, probiotics, and synbiotics on constipation-associated gastrointestinal symptoms and to identify which issues still need to be answered. A literature search was performed in the PubMed database. Animal models (n= 23) and clinical trials (n= 39) were included. In animal studies, prebiotic, probiotic, and synbiotic supplementation showed a decreased colonic transit time (CTT) and an increase in the number and water content of feces. In humans, inulin is shown to be the most promising prebiotic, while B. lactis and L. casei Shirota probiotics were shown to increase defecation frequency, the latter strain being more effective in improving stool consistency and constipation symptoms. Overall, synbiotics seem to reduce CTT, increase defecation frequency and improve stool consistency, with a controversial effect on constipation symptoms improvement. Moreover, some aspects of probiotic use in constipation-related outcomes remain unanswered, such as the best dose, duration, time of consumption (before or during, or after meals), and matrices, as their effect and mechanisms on the regulation of inflammation in patients with constipation, on polymorphisms associated with constipation and on the management of constipation via 5-HT. Thus, more high-quality randomized control trials (RCTs) evaluating these lack aspects are necessary to provide safe conclusions about their effectiveness in managing intestinal constipation.